Prevalence and Prognostic Value of Heart Failure Stages: An Elderly Inpatient Based Cohort Study - Zheng, Pei-Pei; Yao, Si-Min; Guo, Di; Cui, Ling-ling; Miao, Guo-Bin; Dong, Wei; Wang, Hua; Yang, Jie-Fu (Frontiers in Medicine, 2021)
Background: The prevalence and prognostic value of heart failure (HF) stages among elderly hospitalized patients is unclear. Methods: We conducted a prospective, observational, multi-center, cohort study, including hospitalized patients with the sample size of 1068; patients were age 65 years or more, able to cooperate with the assessment and to complete the echocardiogram. Two cardiologists classified all participants in various HF stages according to 2013 ACC/AHA HF staging guidelines. The outcome was rate of 1-year major adverse cardiovascular events (MACE). The Kaplan–Meier method and Cox proportional hazards models were used for survival analyses. Survival classification and regression tree analysis were used to determine the optimal cutoff of N-terminal pro-brain natriuretic peptide (NT-proBNP) to predict MACE. Results: Mean age was 75.3 ± 6.88 years; 4.7% were stage 0; 21.0% were stage A; 58.7% were stage B; and 15.6% were stage C/D. HF stages were associated with worsening 1-year survival without MACE (χ2 = 69.62, P <0.001). Deterioration from stage B to C/D was related to significant increases in HR (3.636, 95% CI, 2.174–6.098, P <0.001). Patients with NT-proBNP levels over 280.45 pg/mL in stage B (HR 2; 95% CI 1.112–3.597; P = 0.021) and 11111.5 pg/ml in stage C/D (HR 2.603, 95% CI 1.014–6.682; P = 0.047) experienced a high incidence of MACE adjusted for age, sex, and glomerular filtration rate. Conclusions: HF stage B, rather than stage A, was most common in elderly inpatients. NT-proBNP may help predict MACE in stage B. Trial registration: ChiCTR1800017204; 07/18/2018.